Chronic suppurative otitis media and its association with sensorineural hearing loss: evidence from a systematic review - Raquib, Ahmed; Taous, Ahmmad (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2026)
Chronic suppurative otitis media (CSOM) remains a major cause of preventable hearing impairment worldwide, yet its association with sensorineural hearing loss (SNHL) is often underestimated. The objective of this systematic review was to evaluate the prevalence, characteristics, and determinants of SNHL among patients with CSOM. A comprehensive literature search was performed across PubMed/MEDLINE, Scopus, Web of Science, and Google Scholar for studies published between January 2000 and February 2025. Eligible studies included patients diagnosed with CSOM who underwent pure-tone audiometry with bone conduction (BC) threshold assessment. Twelve studies met the inclusion criteria, representing 1,742 participants from Bangladesh, India, Pakistan, Iran, and Brazil. SNHL prevalence ranged from 18% to 31%, with significantly higher BC thresholds in diseased ears compared with contralateral normal ears. High-frequency hearing loss was most prominent. Longer disease duration, squamosal CSOM, and subtotal perforations were associated with greater SNHL in several studies, while findings on cholesteatoma were inconsistent. Overall, evidence demonstrates that CSOM contributes meaningfully to SNHL through chronic inflammation and cochlear involvement. Early diagnosis, routine audiological monitoring, and timely intervention are essential to prevent irreversible cochlear damage. Further longitudinal studies are needed to clarify risk factors and guide management.